2019
DOI: 10.1371/journal.pone.0223017
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel West Nile Virus protease inhibitor based on isobenzonafuranone and triazolic derivatives of eugenol and indan-1,3-dione scaffolds

Abstract: The West Nile Virus (WNV) NS2B-NS3 protease is an attractive target for the development of therapeutics against this arboviral pathogen. In the present investigation, the screening of a small library of fifty-eight synthetic compounds against the NS2-NB3 protease of WNV is described. The following groups of compounds were evaluated: 3-(2-aryl-2-oxoethyl)isobenzofuran-1(3H)-ones; eugenol derivatives bearing 1,2,3-triazolic functionalities; and indan-1,3-diones with 1,2,3-triazolic functionalities. The most prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Eugenol is a volatile compound that varies from colorless to light yellow and has low water solubility (approximately 2460 mg/L at 25 • C), a strong odor, and an intense flavor. Among the reported biological activities of eugenol are insecticidal, antimicrobial, anti-inflammatory, wound healing, antiviral, antioxidant, and anticancer activity [13,14,[23][24][25][26][27].…”
Section: Eugenolmentioning
confidence: 99%
“…Eugenol is a volatile compound that varies from colorless to light yellow and has low water solubility (approximately 2460 mg/L at 25 • C), a strong odor, and an intense flavor. Among the reported biological activities of eugenol are insecticidal, antimicrobial, anti-inflammatory, wound healing, antiviral, antioxidant, and anticancer activity [13,14,[23][24][25][26][27].…”
Section: Eugenolmentioning
confidence: 99%
“…Numerous eugenol derivatives bearing triazole functionalities have been successfully accessed through the “click chemistry” approach ( Figure 4 , Scheme 18 ). Several examples are present in the literature about ( i ) O -alkylation of eugenol with terminal alkynes, followed by reaction with different benzyl azides [ 203 , 204 , 205 ]; ( ii ) eugenol conversion in epoxide and ring opening to obtain the corresponding alkyl azides, followed by reaction with different alkynes [ 206 ]; ( iii ) hydroboration oxidation at the allylic position of eugenol, followed by mesylation and azidation reactions, to achieve the eugenol azide; then, reaction with phenylacetylene to afford the triazole. Importantly, the first step of this latter process requires -OH protection trough silylation, thus allowing the synthesis of variously substituted products ( Scheme 18 ) [ 207 ].…”
Section: Monophenolsmentioning
confidence: 99%
“…Synthesized eugenol triazole derivatives showed leishmanicidal [ 205 ], antimycobacterial [ 207 ], trypanocidal [ 206 ], anticancer [ 203 ] as well as protease inhibitory [ 204 ] activity. Triazole eugenol glucosides also showed significant bactericidal activity and low toxicity to normal cells [ 208 ].…”
Section: Monophenolsmentioning
confidence: 99%
“…Eugenol is a volatile compound that varies from colorless to light yellow, has low water solubility (approximately 2460 mg/L at 25 °C), a strong odor, and an intense flavor. Among the reported biological activities of eugenol is insecticide activity, antimicrobial, anti-inflammatory, wound healing, antiviral, antioxidant, and anticancer [7,8,[14][15][16][17][18].…”
Section: Clove Essential Oil (Ceo)mentioning
confidence: 99%
“…The CEO has shown antiviral activity against Ebola [101], influenza A virus [102], herpes simplex virus type 1, and type 2 [101]. Recent studies by de Oliveira et al showed that eugenol derivatives could inhibit the activity of the West Nile Virus, providing a promising compound against flaviviruses, such as dengue virus, Zika virus, and yellow fever virus [15]. Eugenol has also been studied as a possible inhibitor of the initial stage of infection by the HIV-1 virus because it can reduce virus replication.…”
Section: Antiviralmentioning
confidence: 99%